2013
DOI: 10.5194/bg-10-1231-2013
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of soil greenhouse gas fluxes from extensive and intensive grazing in a temperate maritime climate

Abstract: Abstract. Greenhouse gas (GHG) fluxes from a seminatural, extensively sheep-grazed drained moorland and intensively sheep-grazed fertilised grassland in South East (SE) Scotland were compared over 4 yr (2007–2010). Nitrous oxide (N2O) and methane (CH4) fluxes were measured by static chambers, respiration from soil plus ground vegetation by a flow-through chamber, and the net ecosystem exchange (NEE) of carbon dioxide (CO2) by eddy-covariance. All GHG fluxes displayed high temporal and interannual variability. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
40
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(52 citation statements)
references
References 27 publications
12
40
0
Order By: Relevance
“…Given that a recent meta-analysis has demonstrated that vegetation is the strongest explanatory parameter for CH 4 flux variability (Levy et al, 2012), it is likely that the higher CH 4 fluxes measured from the shallow-drained nutrient-poor sites were also a product of the presence of Juncus effusus (aerenchymous species) as seen in other studies Herbst et al, 2013). Overall, our results demonstrate that CH 4 fluxes were negligible, if not absent components of the C balance of extensively drained grasslands over organic soils in a maritime temperate climate, and that CH 4 was emitted only in The absence of N 2 O emissions from the nutrient-poor sites was consistent with the lack of artificial fertiliser use for several decades at these sites, and similar results have been reported from an extensive drained moorland in Scotland (Skiba et al, 2013). In nutrient-rich sites, the potential for N 2 O emissions is much higher, and is additionally forced by fertiliser applications to these more productive systems.…”
Section: Magnitude Of Ch 4 and N 2 O Fluxessupporting
confidence: 89%
See 2 more Smart Citations
“…Given that a recent meta-analysis has demonstrated that vegetation is the strongest explanatory parameter for CH 4 flux variability (Levy et al, 2012), it is likely that the higher CH 4 fluxes measured from the shallow-drained nutrient-poor sites were also a product of the presence of Juncus effusus (aerenchymous species) as seen in other studies Herbst et al, 2013). Overall, our results demonstrate that CH 4 fluxes were negligible, if not absent components of the C balance of extensively drained grasslands over organic soils in a maritime temperate climate, and that CH 4 was emitted only in The absence of N 2 O emissions from the nutrient-poor sites was consistent with the lack of artificial fertiliser use for several decades at these sites, and similar results have been reported from an extensive drained moorland in Scotland (Skiba et al, 2013). In nutrient-rich sites, the potential for N 2 O emissions is much higher, and is additionally forced by fertiliser applications to these more productive systems.…”
Section: Magnitude Of Ch 4 and N 2 O Fluxessupporting
confidence: 89%
“…The NEE values for the nutrient-poor shallowdrained sites in this study represent similar sinks (small source in some years) to those reported by Skiba et al (2013) for grazed drained nutrient-poor organic soils (moorland) in a maritime temperate climate. Our results would therefore point to the significance of edaphic conditions as well as the low intensity management system encountered at our sites.…”
Section: F Renou-wilson Et Al: the Impacts Of Drainage Nutrient Stsupporting
confidence: 85%
See 1 more Smart Citation
“…However, a significant amount of snow fell, which was not recorded by the wet-only collector. Based on the ratio of discharge and precipitation Skiba et al, 2013) it was estimated that snow accounted for an additional 291 mm, making the total precipitation collected for 2010 approximately 1023 mm. The mean monthly temperature varied from −2.0 • C in December to 13.6 • C in July, with a yearly mean of 6.6 • C. …”
Section: Meteorologymentioning
confidence: 99%
“…Many papers suggested, that soil moisture and type of fertilization are key determinants of the microbial processes (Natywa et al, 2014), that determine the fluxes of GHG from soil (Nannipieri et al, 2003;Skiba et al, 2013).…”
Section: Introductionmentioning
confidence: 99%